Metaphor and imagery in Persian poetry - Seyed-Gohrab, A. A. 1968- (Iran Studies, 2012)
This volume is a collection of essays on classical Persian literature, focusing on Persian rhetorical devices, especially imagery and metaphors. The various contributions discuss the origin and the development of debate poetry, the transmission of Persian and Arabic tales to the works of Europeans medieval authors such as Boccaccio and Chaucer, but also the development of Aristotelian poetics and epistemology in Persian philosophical tradition. Furthermore, the baroque style of the Shiʿite author Ḥusayn Vāʾiẓ Kāshifī, the use of wine metaphors by mystics such as Jalāl al-Dīn Rūmī, Ḥāfiẓ's original use of candle metaphors, the translation of Khayyām's metaphors into English, and the importance of a single metaphor in the epic Barzū-nāma are discussed. Contributors include: F. Abdullaeva, G.R. van den Berg, J. Landau, F.D. Lewis, N. Pourjavady, Ch. van Ruymbeke, A. Sedighi and S. Sharma